Complaint behavior intentions and expectation of service recovery in individualistic and collectivistic cultures. Issue 3 (29th July 2014) - Gi Park, Seul; Kim, Kyungmi; O'Neill, Martin
Abstract : Purpose: – The purpose of this study is to investigate whether complaint behavior intentions and expectations of service recovery based on the justice theory are different among customers from collectivistic versus individualistic cultures. A secondary purpose is to find which service recovery strategies are appropriate for different culture-based complaint behavior intentions. Design/methodology/approach: – A survey was conducted at universities, and the survey population consisted of college students, who are known to be frequent users of fast-food restaurants. A total of 304 usable questionnaires were collected. Confirmatory factor analysis was conducted to verify the validity of the items, Cronbach's alpha coefficients were used to examine the internal consistency of the factors, and an independent sample t -test was used to analyze differences in complaint behavior intentions and expectations of service recovery efforts in terms of cultural difference. Findings: – The results of this study indicated that South Koreans revealed more voice complaint behavior intentions than Americans did. However, there were no significant differences in expectations of service recovery efforts between them. Second, American customers who indicated voice and private complaint behavior intentions expected distributive, procedural and interpersonal justice in complaint-handling procedures. South Korean customers who indicated voice complaint behavior intentions expected distributive and procedural justice, and South Korean customers who indicated private complaint behavior intentions anticipated interactional justice in complaint-handling procedures. Research limitations/implications: – Understanding customers' complaint behavior intentions and expectations of service recovery based on the justice theory and cultural differences will suggest practical implications to hospitality industry managers for effective service quality management. Originality/value: – Understanding customers' complaint behavior intentions and expectations of service recovery based on the justice theory and cultural differences will suggest practical implications to hospitality industry managers for effective service quality management.